Architecture in the age of artificial intelligence : an introduction for architects - Leach, Neil (London ; New York : Bloomsbury Visual Arts, 2021)
"Artificial intelligence is everywhere - from the apps on our phones to the algorithms of search engines. Without us noticing, the AI revolution has arrived. But what does this mean for the world of design? The first volume in a two-book series, Architecture in the Age of Artificial Intelligence introduces AI for designers and considers its positive potential for the future of architecture and design. Explaining what AI is and how it works, the book examines how different manifestations of AI will impact the architectural profession. Highlighting current case-studies as well as near-future applications, it shows how AI is already being used as a powerful design tool, and how AI-driven information systems will soon transform the future of buildings and cities. Far-sighted, provocative and challenging, yet rooted in careful research and cautious speculation, this book, written by architect and theorist Neil Leach, is a must-read for all architects and designers - including students of architecture and all design professionals interested in keeping their practice at the cutting edge of technology"--
What is AI? -- The history of AI -- AI, art and creativity -- AI, media art and neuroscience -- AI and architecture -- The future of the architectural office -- AI and the city of the future -- The future of AI.
Includes bibliographical references and index.
ARC
Keywords: Architecture and technology; Artificial intelligence; Architecture